The Pengaruh Infeksi Plasmodium sp. Terhadap Trombosit Manusia: Tinjauan Literatur - Avichena, Avichena; Anggriyani, Ria (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2023)
Malaria is a health problem that can cause death. Research based on a literature review shows that malaria is an infectious disease that causes high morbidity worldwide and is the third leading cause of death in the world. Malaria is caused by Plasmodium infection of red blood cells, Plasmodium infection can cause various symptoms in humans, especially in platelets. The purpose of this study was to find out how the effect of Plasmodium sp. infection. Against Human Platelets. This research method uses a literature review (literature review). Literature review is research by searching and mapping literature. This research was conducted using various sources, including books, journals, magazines, and articles. Based on research, Plasmodium infection can disrupt the structure and function of platelets. Almost all blood components are affected by malaria. The risk of malaria is caused by environmental factors. the mobility of malaria sufferers at school and productive age, whose activities are mostly outside the home, makes them very vulnerable to malaria, because they are more often affected than people who do a lot of activities outside the home. So it can be concluded that malaria is influenced by environmental factors. The variability and range of environmental influences on malaria mediators is enormous